A Person First: a workshop to help teens support friends with mental problems - Edzerza, Debra G. (Author); Brown, Willow (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2014)
The author of this study, a First Nations teacher, has designed a culturally sensitive workshop for northern youth addressing mental health concerns. The ten hour workshop, entitled A Person First!, will encourage youth to consider the harmful impact of stigma on people who have mental health issues. The need for a workshop that appeals specifically to First Nations youth is evident in Yukon and in other northern communities, currently there is a lack of culturally relevant workshops that addresses mental health issues in remote northern communities. A Person First! Is geared towards First Nations learners and will be presented n the context of the cultural beliefs systems within their own communities. The author has presented a leader's guide for local facilitators that includes instructions for the use of video clips, circle discussions, and a self-reflection tool based on the Medicine Wheel. The workshop design, supported by research, recommends community education to promote youth resilience through stigmas reduction and peer support. As community-based education, this workshop was designed to stimulate transformative change in youth thinking and behavior so that peers experiencing mental health issues will experience a supportive environment. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b2006878